Engineering Gology Model of Bener Dam Diversion Tunnels in Geological Risk Disaster Mitigation - Daru Jaka Sasangka; Dian Insani; I Gde Budi Indrawan (Engineering Faculty Universitas Lampung, 2020)
The Bener Dam Diversion Tunnel Plan is located in Bener District, Purworejo Regency. Engineering geology mapping data, drillimg data and laboratory data used as primary data. Surface and subsurface analysis show that each rock unit has different index and mechanical properties. Generally, the rock mass quality conditions in the dam belonged to good Rock (80%) in the Rock Mass Rating (RMR) system (Bieniawski, 1989). The other rock mass quality type also found among them fair rock (5%), poor rock (5%), and very poor rock (10%). Poor rock mass quality conditions were controlled by geological structures, especially faults that partially cut through the tunnel geometry. The very poor quality of rock mass was in the volcanic lens (loose sand material) did not cut through the tunnel path. The difference stand-up time of the rock on the tunnel requires proper mitigation (Nguyen Nguyen, 2015). The stand-up time belonged to the dangerous condition was in the fault zone with poor rock mass quality, while the lens with very bad rock mass quality did not affect the stability of the excavation of the tunnel.